Peningkatan Kreativitas dan Hasil Belajar IPA Materi Zat Aditif dan Zat Adiktif melalui Penerapan Metode Mind Map dan Index Card Match - Gotri Lastiti (Paedagogie, 2020)
The purpose of this study was to increase students’ creativity and science learning outcomes. It was conducted in SMP N 1 Bawang. It employed Classroom Action Research carried out within 2 cycles. The methods used in the learning process mind map and index card match. Data were obtained through tests and observations. In the first cycle, there were 59.38% of students who showed a good predicate of creativity. The completeness of learning outcomes is 75% with an average of 73.47. In the second cycle, there were 81.25% of students who were included in the good creativity category. The completeness of learning outcomes is 90.63% with an average of 81.63. The application of this method gives an impact on increasing creativity and students’ learning outcomes.